(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The Orange Book formally Approved Drug Products with Therapeutic Equivalence Evaluations is a cornerstone resource in pharmaceutical regulation. Published by the U.S. Food and Drug Administration (FDA), it serves as the authoritative reference for identifying drug products that have been rigorously evaluated for safety, efficacy, and therapeutic equivalence. Mandated under the Federal Food, Drug, and Cosmetic Act, the Orange Book lists FDA-approved medications and provides comprehensive information on associated patents and marketing exclusivity periods. This compendium promotes transparency and regulatory certainty, enabling healthcare professionals, consumers, and industry stakeholders to make informed decisions. Its alignment with the Hatch-Waxman Act strikes a strategic balance between encouraging pharmaceutical innovation and enabling timely generic market entry. By detailing patent expiration dates and exclusivity periods, the Orange Book gives generic manufacturers critical insights for planning Abbreviated New Drug Applications (ANDAs) and navigating the generic approval pathway. Because it includes only products that meet stringent FDA standards, the Orange Book reinforces public confidence in medication quality and safety. By fostering generic competition, it helps reduce drug costs and expand access to essential therapies, underscoring its importance for public health and a balanced pharmaceutical ecosystem.